The influence of organizational climate and organizational culture on the performance of employees of the tourism and creative economy office of DKI Jakarta province with motivation as an intervening variable - Trisha Miria Gayatri; Sri Lestari Prasilowati (Sean Institute, 2024)
The current condition of employee performance at the DKI Jakarta Provincial Tourism and Creative Economy Office is felt to be not optimal. This can be seen from the target performance targets, both specific and general targets, in some indicators that have not reached the target. It is indicated that several factors influence it, including organizational climate factors, organizational culture, and employee motivation in carrying out their duties. The research was carried out at the DKI Jakarta Provincial Tourism and Creative Economy Office with a research population of 84 employees; due to population limitations, the sample used was a saturated sample of 84 respondents for data collection using questionnaire method techniques and direct observation. For data analysis using the Smart Partial Least Square (PLS) analysis method version 3.0, the data tests used in this study are reliability tests, validity tests, statistical tests, and classical assumption tests. The direct influence of organizational culture is more dominant when compared to organizational climate, and the indirect influence of organizational culture is more dominant when compared to organizational climate. Organizational culture and organizational climate both directly and indirectly have the same influence. Implementing organizational culture through the development of innovation and risk-taking by giving freedom to employees to develop innovation and freedom of action also involves employees in making a vision and mission and discipline in carrying out their main duties for the organizational climate to create a harmonious relationship with the team. Employees are free to interact with the team to create relationships between teams, motivation to provide workload and responsibility in completing work results, awards for outstanding employees, and opportunities to advance.